Tunable structuring of nanocellulose-based sustainable lubricants by an external electric field - Samuel D. Fernández-Silva; Miguel A. Delgado; María García-Pérez; Claudia Roman; Moisés García-Morales (Journal of Materials Research and Technology)
This research investigates the morphological and electrorheological (ER) behaviors of nanocellulose-based lubricants. Commercial fibrillated (CNF) and crystalline (CNC) nanocelluloses were dispersed in castor oil, at two selected concentrations of 1 and 4 wt%, to obtain fully sustainable electro-active lubricants. Small amplitude oscillatory shear (SAOS) tests were performed within the linear viscoelastic (LVE) range to investigate the rheological behavior induced by the combined effect of pre-shear and voltage. Hence, prior to the SAOS tests at electric field intensities ranging from 0 to 4 kV/mm, the samples were subjected to simple shear, at two selected values of 0.1 and 30 s−1 and for 5 min, under the same voltages. A portable digital microscope, attached to a strain-controlled rheometer, allowed visualizing the electro/shear-induced structuring of the lubricants and establishing relationships with their rheological response. In general, both storage and loss moduli were found to change with the electric field. Regarding the effect of nanocellulose concentration, the formation of thin strings was observed at 1 wt% nanocellulose when the lubricant was subjected to low pre-shear. Their angular displacement increased with the electric field. On the contrary, at 4 wt% nanocellulose, a fully entangled network was perceived, such that the nanofiber rotation was severely restrained. The highest pre-shear yielded a structural break which, under the action of an electric voltage, enabled the formation of a different structural conformation when pre-shear halted, in comparison with the lowest pre-shear. Such event led to a notorious reduction in both storage and loss moduli, mainly at the lowest electric field intensities.